Fundamental limitations for electroluminescence in organic dual-gate field-effect transistors - Roelofs, W. S. Christian; Spijkman, Mark-Jan; Mathijssen, Simon G. J.; Janssen, René A. J.; Leeuw, Dago M. de; Kemerink, Martijn (Advanced materials, 2014)
A dual-gate organic field-effect transistor is investigated for electrically pumped lasing. The two gates can independently accumulate electrons and holes, yielding current densities exceeding the lasing threshold. Here, the aim is to force the electrons and holes to recombine by confining the charges in a single semiconducting film. It is found that independent hole and electron accumulation is mutually exclusive with vertical recombination and light emission.